How much blood is needed? - Seifried, Erhard; Klüter, Harald; Weidmann, Christian; Staudenmaier, T.; Schrezenmeier, H.; Henschler, R.; Greinacher, A.; Mueller, M. M. (Vox sanguinis, 2011)
Demographic changes in developed countries as their populations age lead to a steady increase in the consumption of standard blood components. Complex therapeutic procedures like haematopoietic stem cell transplantation, cardiovascular surgery and solid organ transplantation are options for an increasing proportion of older patients nowadays. This trend is likely to continue in coming years. On the other hand, novel aspects in transplant regimens, therapies for malignant diseases, surgical procedures and perioperative patient management have led to a moderate decrease in blood product consumption per individual procedure. The ageing of populations in developed countries, intra-society changes in the attitude towards blood donation as an important altruistic behaviour and the overall alterations in our societies will lead to a decline in regular blood donations over the next decades in many developed countries. Artificial blood substitutes or in vitro stem cell-derived blood components might also become alternatives in the future. However, such substitutes are still in early stages of development and will therefore probably not alleviate this problem within the next few years. Taken together, a declining donation rate and an increase in the consumption of blood components require novel approaches on both sides of the blood supply chain. Different blood donor groups require specific approaches and, for example, inactive or deferred donors must be re-activated. Optimal use of blood components requires even more attention.